Digital Transformation in Enterprise Risk Management: A Bibliometric Study and Research Trends - Judijanto, Loso; Pahrijal, Rival; Lesmana, Tera (West Science Social and Humanities Studies, 2025)
This study examines digital transformation research using bibliometric analysis, identifying key trends, collaborative networks, and thematic areas. Findings reveal that "digital transformation" is central, closely linked to "decision making," "artificial intelligence," and "risk assessment." Over time, research has shifted from broad technological advancements to domain-specific applications like healthcare and telemedicine. Co-authorship analysis highlights strong academic networks, particularly in the U.S., U.K., and China, though interdisciplinary collaboration remains a challenge. The study emphasizes the need for ethical AI governance, enhanced cybersecurity, and inclusive global research participation to ensure balanced technological progress.